Problematyka sił społecznych środowiska wychowawczego (Wprowadzenie do koncepcji) - Olubiński, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The author discusses a problem of actions of educational activation of environment. A central national category linked with that problem and focussing the attention of this study is a term of „social strength". The author attempts at defining that notion, attribute operational meaning to it indicate at defined types of social strength. The most general meaning of that term pertains to a complex of defined factors, phenomena and processess of a psycho-social and educational character, situated in the institutions of natural, indirect and direct education. They cause a process of transforming these institutions into a favorable educational environment. In the following part, three basic, closely interrelated elements of strength are defined: i.e. 1) type and character of educational institution in the environment (e.g. family, school, workplace etc.), 2) material structure of essential elements contained in those institutions (e.g. material and standard of living factors, cultural, psychological, social, demographic, educational ones, etc.), 3) agents and dynamisms activating in a form of natural social processess (e.g. conflicts, adaptation, industrialization, urbanization, etc.). In turn, in the context of social strength study, the author attempts at defining a role of intentional educational activity. A specific approach to educational process is effected by the analysis: it is understood as a sequence of changes of personality and environment answering to goals of education, achieved in the effect of dynamic relation of planned educational activity and social strength supporting these actions. The discussion is concluded with remarks on educational environment. The authors draws his attention at a role of the so-called endogenous factors of social changes (e.g. conflicts) as positive elements in educational activation of the environment. In this way the author attempts to expand a sociological handling, of an educational environment (territorial) also by means of an extra-territorial viewpoint.
Problems of social strength in educational environment